The infectious diseases clinical research program acute respiratory infection repository protocol: Opportunities to understand current and future epidemics - Simon D. Pollett; Rhonda E. Colombo; Stephanie A. Richard; Tahaniyat Lalani; Brianne Barton; Allison Malloy; Anthony Fries; Edward Parmelee; Scott Merritt; Mark Fritschlanski; Edward E. Mitre; Eric D. Laing; et al. (PLoS ONE, 2025)
Background Acute respiratory infections (ARI) are a major cause of morbidity and lost workdays in both military and non-military populations. To better understand these infections and their outcomes, the Infectious Diseases Clinical Research Program has enabled nine major ARI clinical research protocols in the last decade, including observational studies and trials, spanning emerging and reemerging ARI threats including Severe Acute Respiratory Syndrome Coronavirus 2, influenza, adenovirus, entero/rhinovirus, human metapneumovirus, respiratory syncytial virus, and other pathogens. These protocols have resulted in epidemiological, clinical and laboratory data and biospecimens from over 26,000 participants, most of whom were beneficiaries of a geographically distributed Military Health System. Methods The Acute Respiratory Infection Repository Protocol establishes a unique Department of Defense (DoD) research resource through the pooling of data and specimens from nine ARI protocols into a master, standardized database with a linked specimen repository. This will enable further targeted scientific questions in participant-level pooled meta-analyses and will serve as an on-demand repository for rapid assay development, sample size estimations for prospective studies, and observational study/clinical trial design (including as part of future rapid pandemic research response). Accordingly, the objectives and study design of this protocol are broad. This protocol will allow analyses on outcomes including: (i) short-term ARI outcomes such as hospitalization, work days lost, symptom severity and duration; (ii) post-acute ARI outcomes, including persistence of symptoms, return-to-health, post-ARI medical encounters; (iii) vaccine effectiveness for Coronavirus disease 2019 (COVID-19), influenza, and adenovirus vaccines; (iv) ARI infection and vaccination elicited immune responses (humoral, T-cell, other); (v) therapeutic effectiveness of COVID-19 and influenza antivirals (acute symptoms, hospitalization, post-acute sequelae); (vi) effectiveness of non-pharmaceutical interventions (e.g., masking) against infection; (vii) prognostic and mechanistic host viral biomarkers which correlate with the above outcomes; (viii) ARI diagnostic assay validity and performance. This repository protocol is inherently broad in scope; the collation of standardized data and phenotype-linked specimens is a fundamental, primary objective. Discussion This protocol will support statistical and laboratory analyses, including activities related to rapid epidemic response such as assay development and rapid sample size calculations for clinical trials. A series of more specific scientific questions from current and future collaborators will leverage this joint database and specimen repository; these questions will target important aspects of ARI infection, transmission, outcomes, and treatment. Future protocols (and ongoing data from existing IDCRP protocols) will be added to this collaborative repository protocol.